OVERCOMING GENDER AND RACIAL BIAS IN THE WORKPLACE: AN EXAMINATION OF AMAZON’S PERFORMANCE EVALUATION PRACTICES - Alejandro Lopez; Brian Marquez; David Martinez; Nina Lozovnoy (Current Journal of Human Resource Management (CJHM), 2023)
Gender and racial discrimination persist as critical challenges in modern corporations, leading to biased decisions and inequities for minority groups. This paper examines Amazon’s gender and racial discrimination practices in employee performance evaluation. Despite Amazon’s commitment to diversity and inclusion, several lawsuits filed against the company by women of color indicate significant discrepancies in its performance evaluation practices. This paper explores the causes, consequences, and ways to reduce bias in Amazon’s workplace to encourage a more diverse and inclusive work environment. Recruitment and hiring processes should avoid prejudice or bias and instead, encourage diverse background talent and ideas. Amazon recruiters should be intentionally selected to include individuals from diverse backgrounds, race, ethnicity, gender, and ability-wise, to broaden the organization’s perspective. Initiatives specifically targeting the growth of minorities should be implemented, reflecting the diverse policies promoted on the company’s website. Amazon should establish clear-cut criteria for evaluating potential candidates to ensure fairness and equality in the recruitment process. Implementing training sessions around topics like cultural competence and implicit bias would allow employees to better understand and respect their co-workers from different backgrounds. Versatile mentoring and training programs would be incorporated into the company work schedule biannually or more frequently to emphasize the importance of diversity and inclusion regularly. Finally, Amazon’s work environment should be healthy for everyone, regardless of their skin color, race, sexuality, or ethnicity, promoting an inclusive and supportive learning atmosphere.